قضايا الارتباط بين ضرورات اجتهاد القاضي الإداري ومحدودية الشرعية الإجرائية - سلطاني, آمنة (جامعة الوادي.University eloued, 2022)
عتبر الارتباط بين الدعاوى والطلبات و الدفوع ممارسة خلافية شائعة أمام المحاكم الإدارية ، سواء في الدرجة الأولى أو الاستئناف، ومع ذلك، لم يرد ذكر هذه الممارسة في الكتاب الرابع الخاص بالإجراءات المتبعة أمام الجهات القضائية الإدارية و ضمن قانون الإجراءات المدنية والإدارية رقم 08-09 المؤرخ في 25 فبراير 2008 على نحو تفصيلي على عكس ما قد يوجد في الإجراءات المدنية أو الجنائية على سبيل المثال ؛ ما يعكس محدودية وجود مرجعية في الشرعية الإجرائية الإدارية ؛ تُبين المعايير المستخدمة في قضايا الارتباط و الحلول المكننة حال استحالة التطبيق على الواقع في هذا الصدد نشير إلى مجموعة من الأسئلة التي نقترحها في هذا المقال حول ضرورات اجتهاد القاضي الإداري في قضايا الارتباط فهل يمكنه أن يقرر من تلقاء نفسه الإحالة لوجود الارتباط إذا رغب في ذلك أم هو غير ملزم أبدًا ؛ إلا عندما يطلب ذلك من قبل الخصوم ؛و ماذا عن مسألة إحالة النزاع من قبل جهة القضاء ؟ ، على فرض أن القاضي الإداري يتمتع منذ بداية القرن العشرين بحرية كبيرة تجاه استنتاجات الأطراف؛ أي حقيقة أن الارتباط ليس سوى إجراء للتخفيف من حدة وصعوبة الإجراءات أو ما يسمى بالإدارة الجيدة للعدالة ومن ضمن أهم اعتبارات وقواعد الحكامة الجيدة التي بات يروج لها كمبدأ قضائي فريد من نوعه ، وهي التي تدفع القاضي في معظم الأحيان إلى ربط الدعاوى أو الطلبات ، لا سيما عندما يصبح حل نزاع يتألف من عدة فروع أكثر وضوحًا أو عندما يتيح شكلاً من أشكال عدم التناقض في عرض الحقائق أو الوسائل.The connection between lawsuits, requests, and defenses is considered a common contentious practice before administrative courts, whether in the first degree or on appeal. However, this practice was not mentioned in the fourth book on the procedures followed before the administrative judicial authorities and within the Civil and Administrative Procedures Law No. 09-08 dated on February 25, 2008 in a detailed manner unlike what might be found in civil or criminal proceedings for example; Which reflects the limited existence of a reference in administrative procedural legitimacy; The standards used in association cases and automated solutions indicate the impossibility of application to reality. In this regard, we refer to a set of questions that we propose in this article about the necessities of the administrative judge’s diligence in association cases. Can he decide on his own to refer the existence of association if he so desires, or He is never obligated; Except when it is requested by the litigants; and what about the issue of referring the dispute by the judiciary? Assuming that, since the beginning of the twentieth century, the administrative judge enjoys great freedom with regard to the conclusions of the parties; In other words, the fact that association is only a measure to mitigate the severity and difficulty of procedures or what is called good administration of justice and among the most important considerations and rules of good governance that is now being promoted as a unique judicial principle, and it is what prompts the judge most of the time to link lawsuits or requests, especially When the resolution of a dispute consisting of several strands becomes clearer or when it allows some form of non-contradiction in the presentation of facts or means.
مجل- 01 العدد 02
Keywords: الارتباط، الطلبات، الدعاوى، الإحالة، الدفوع; Association, Applications, Claims, Referrals, Defenses